Primary Myeloid Sarcoma of the Prostate: A Case Report and Literature Review - Ryan Nguyen; Hamid Sayar (Case Reports in Hematology)
We report the case of a 73-year-old male with primary myeloid sarcoma (MS) of the prostate. He underwent remission-induction chemotherapy followed by conventional consolidation for acute myeloid leukemia (AML). One year after initial diagnosis, he was without evidence of AML, the longest reported period of time in the literature for a case of primary MS of the prostate. From 1985 to 2017, fifteen other cases of MS of the prostate have been reported and are reviewed here. Five cases occurred as primary MS, without evidence of AML on bone marrow examination or prior history of hematologic disorders, and progressed to AML within a range of three weeks to seven months. None of these cases were started on conventional chemotherapy for AML prior to progression. Due to its rarity, primary MS of the prostate is often diagnosed incidentally, but prompt AML-targeted treatment is crucial to delaying the progression to AML.